Two Cases of Delayed Diagnosis of Leprosy in Mauritania - Boushab Mohamed Boushab; Fatima-Zahra Fall-Malick; Leonardo K. Basco (Case Reports in Dermatological Medicine)
Leprosy is a chronic infectious disease that mainly affects the skin, mucous membranes, and peripheral nervous system. The clinical manifestations of leprosy are numerous and polymorphic with the most frequent signs involving skin and neurological damage. Some of its manifestations, such as joint pain, are unusual. Its elimination as a public health problem in many countries seems to lead to a lack of practical knowledge among health care personnel and as a consequence a risk of late diagnosis. As in other countries, leprosy has become rare in Mauritania. We report two cases of misdiagnosed leprosy in two male patients aged 17 and 65 years. Clinical manifestations included polyarthritis, bilateral plantar perforation, and severely deformed hands and feet in the first case and lichenoid lesions, hypopigmented papules, and unilateral bronchial rales in the second case. The duration of development and persistence of clinical signs before establishment of correct diagnosis was seven to ten years despite the presence of anesthetic, hypochromic maculopapular skin lesions and neurologic signs suggestive of leprosy in both cases. A multilevel chemotherapeutic regimen recommended by the World Health Organization (WHO) was effective, and the patients’ condition evolved satisfactorily. The scarcity of leprosy in our health care facilities often leads to a wrong diagnosis. It is imperative to inform physicians to increase their vigilance for appropriate screening and reporting of these cases. The prognosis depends largely on early diagnosis and appropriate treatment.